2017
DOI: 10.3920/bm2016.0022
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Lactobacillus plantarum strain in honey bee digestive tract monitored using gfp fluorescence

Abstract: Lactic acid bacteria are symbiotic bacteria that naturally reside in the gastrointestinal tract of honey bees. They serve a multitude of functions and are considered beneficial and completely harmless. In our experiments Lactobacillus plantarum strain B35, isolated from honey bee digestive tract, was modified using pAD43-25 plasmid carrying a functional GFP gene sequence (gfpmut3a) and used as a model for monitoring and optimisation of the mode of application. The establishment of this strain in honey bee dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Among LAB, Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) [48] is a versatile bacterium characterized by a high adaptability to many different conditions, being isolated from various ecological niches including dairy, fruits, cereal crops, vegetables, fish and fresh meat [49]. In addition, its presence in honeybee gut has been documented by several researchers [50][51][52], and its role, along with other bacteria and yeasts, in the transformation of fresh pollen into bee bread is well known [53,54]. L. plantarum pro-technological properties are exploited in different agri-food sectors [55][56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…Among LAB, Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) [48] is a versatile bacterium characterized by a high adaptability to many different conditions, being isolated from various ecological niches including dairy, fruits, cereal crops, vegetables, fish and fresh meat [49]. In addition, its presence in honeybee gut has been documented by several researchers [50][51][52], and its role, along with other bacteria and yeasts, in the transformation of fresh pollen into bee bread is well known [53,54]. L. plantarum pro-technological properties are exploited in different agri-food sectors [55][56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…Among the fluorescent markers used in LAB, GFP, RFP, and their derivatives are commonly employed (Landete et al, 2016;Javorský et al, 2017;Spacova et al, 2018). Cellular auto-fluorescence emission of WCFS1 has an intensive wavelength overlap with that of eGFP (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of the Lpb. plantarum strain B35 labeled with GFP were monitored in the digestive tract of honey bees (Javorský et al, 2017). In our previous study, the fluorescence emitted from eGFP protein in Lpb.…”
Section: Introductionmentioning
confidence: 99%
“…It has been isolated in many different environmental niches, such as fruit, vegetables, all types of fermented foods, meat and fish [ 31 , 32 , 33 ]. L. plantarum strains have also been isolated from different honeybee species [ 34 , 35 , 36 , 37 ]. Several authors have demonstrated that L. plantarum colonizes the adult Drosophila melanogaster gut and that it influences different aspects of the insect’s development and life, exerting a growth-promoting effect on larvae under nutrient scarcity [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have proved that L. plantarum has a broad capacity to inhibit the growth of different pathogens, and different strains exert inhibitory activity towards bacteria and fungi. In addition, chemically different compounds with antibacterial and antifungal activity have been characterized in culture filtrates [ 43 , 44 , 45 , 46 ], L. plantarum also exhibits antagonist activity against Paenibacillus larvae , the causative agent of the quarantine disease American foulbrood, which affects A. mellifera larvae and pupae [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Over the years, several studies have obtained relevant data supporting the probiotic properties of L. plantarum [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%